Enhancing sustainable human and environmental health through nexus planning - Nhamo, L.; Mpandeli, S.; Nhamo, S. P.; Liphadzi, S.; Mabhaudhi, Tafadzwanashe (Elsevier, 2022)
A combination of climate change and accelerated population growth is instigating some of the worst challenges that humankind faces today that include resource depletion and degradation. Both built environment and ecological infrastructure have been modified and are creating novel socioecological interactions posing the risk of novel infectious diseases transmission to humans. The experiences of the COVID-19 exposed the vulnerability of human health from wildlife and the risk of novel socioecological interactions on livelihoods. This chapter enhances the preparedness and improves the resilience against novel pathogens by assessing vulnerability and the available options to reduce risk through the water–health–ecosystem–nutrition nexus. As a transformative, nexus planning provides integrated pathways toward resilience and preparedness to reduce health risks on humans posed by novel pathogens. A systematic review of literature facilitated an understanding of the trends of novel infectious diseases and the available options to improve sanitation, nutrition, and adaptative capacity in the advent of novel socioecological interactions. The aim is to guide policy formulations to achieve Sustainable Development Goals such as 3 (good health and wellbeing), 6 (clean water and sanitation), and 13 (climate action). Risk reduction framing in the health sector through nexus planning provides pathways toward healthy environments and mutual socioecological interactions.